Report of deep-sea epibiont ciliates (Ciliophora) from more than 1000 m depth of the Arabian Sea, Indian Ocean - Chatterjee, Tapas; Sautya, Sabyasachi; Dovgal, Igor; Gaikwad, Santosh; Choudhury, Amita (Zootaxa, 2022)
The present article deals with the report of 7 suctorian epibiont species viz. Thecacineta calix, Actinocyathula homari, Loricophrya bosporica, L. cf. stresemanni, Acinetides gruberi, Trematosoma rotunda and Brachyosoma sp. on benthic meiofauna collected from the deep Arabian Sea (> 1000 m). The data on the distribution and host prevalence of found species are discussed. The finds of other deep-sea ciliate species are also mentioned.